Benefits of Improper Signaling for Underlay Cognitive Radio - Lameiro, Christian; Santamaría, Ignacio; Schreier, Peter J. (IEEE Wireless Comm. Lett.)

Analysis of maximally improper signalling schemes for underlay cognitive radio - Lameiro, Christian; Santamaría, Ignacio; Schreier, Peter J. (Proc.\ IEEE Int.\ Conf.\ Comm.)
In this paper, the impact of improper Gaussian signaling is studied for an underlay cognitive radio (CR) scenario comprised of a primary user (PU), which has a rate constraint, and a secondary user (SU), both single-antenna. We first derive expressions for the achievable rate of the SU when it transmits proper and maximally improper Gaussian signals (assuming that the SU is solely limited by the CR constraint). These expressions depend on the channel gains to and from the SU through a single variable. Thereby, we observe that improper signaling is beneficial whenever the SU rate is below a threshold, which depends on the signal-to-noise ratio (SNR) and rate requirement of the PU. Furthermore, we provide bounds on the achievable gain that also depend only on the PU parameters. Then, the achievable rate is studied from a statistical viewpoint by deriving its cumulative distribution function considering a constant received SNR at the PU. In addition, we specialize this expression for the Z interference channel, for which the expected achievable rate is also derived. Numerical examples illustrate our claims and show that the SU may significantly benefit from using improper signaling.

Overdemodulation for high-performance receivers with low-resolution ADC - Stein, Manuel; Sebastian, Theiler; Nossek, Josef A. (IEEE Wireless Comm. Lett.)

Determining the number of correlated signals between two data sets using PCA-CCA when sample support is extremely small - Song, Y.; Schreier, P. J.; Roseveare, N. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Model-order selection for analyzing correlation between two data sets using CCA with PCA preprocessing - Roseveare, N.; Schreier, P. J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Detection of multivariate cyclostationarity - Ramírez, D.; Schreier, P. J.; Via, J.; Santamaria, I.; Scharf, L. L. (IEEE Trans. Signal Processing)

Near-field measurement of stochastic electromagnetic fields - Russer, Johannes A.; Uddin, Nasir; Awny, Ahmed Sanaa; Thiede, Andreas; Russer, Peter (IEEE Electromagnetic Compatibility Magazine)
Keywords: Electrical and Electronic Engineering; Computer Networks and Communications; Instrumentation; Signal Processing; Software

High speed static frequency divider design with 111.6 GHz self-oscillation frequency (SOF) in 0.13 µm SiGe BiCMOS technology - Ali, U.; Bober, M.; Thiede, Andreas; Awny, A.; Fischer, G. (2015 German Microwave Conference)

100–166 GHz wide band high speed digital dynamic frequency divider design in 0.13 μm SiGe BiCMOS technology - Ali, U.; Bober, M.; Thiede, A.; Wagner, S. (2015 10th European Microwave Integrated Circuits Conference (EuMIC))

Low power fundamental VCO design in D-band using 0.13 µm SiGe BiCMOS technology - Ali, U.; Fischer, G.; Thiede, Andreas (2015 German Microwave Conference)